CFD Simulation of Mixing in Rotary Energy Recovery Device - Liu, Kai; Zheng, Lixing (New Approaches in Engineering Research Vol. 6, 2021)
The rotary energy recovery device (RERD) is widely equipped in desalination to reduce the system energy consumption. In this study, the fluid dynamics and mixing performance of a typical structure RERD and a visualization apparatus of a RERD (V-RERD), had been compared by simulation. The effects of rotating components on fluid dynamics and mixing had been researched. Simulation results indicated that a swirling flow can be observed from flow fields in the device duct. In the RERD case, the swirling flow changed its rotating direction in the center of the duct, while in the V-RERD case its rotating direction unchanged. Then, a swirling number Sn was applied to characterize the degree of swirl intensity, and its formation mechanism in RERD had been discussed. In addition, the Q criterion was adopted to visualize the three-dimensional flow structures and identify vortex structures in the duct. The evolution of vortices in the working process had been investigated. It was found that vortices significantly affected the mixing performance, and the detached vortex could lead to high turbulence and mixing in the duct. Suppressing the vortex shedding may reduce the flow turbulence and gain a lower volumetric mixing rate.